Error Estimates for the Finite Element Solutions of Some Variational Inequalities with Nonlinear Monotone Operator (Journal of Computational Mathematics, 1983)
In this paper, we estimate the error of the linear finite element solutions of the obstacle problem and the unilateral problem with monotone operator. We obtained $O(h)$ error bound for the obstacle problem and $O(h^{3/4})$ error bound for the unilateral problem. And if the solution $u^*$ of the unilateral problem possesses more smoothness, then $O(h)$ error bound can be obtained in the same way as [2].